The design management as differential quality in the furniture industry of Alto Uruguai Gaúcho - Silva, José Paulo Medeiros da; Beltrame, Thiago Favarini; Schmidt, Alberto Souza (Revista de Administração da UFSM, 2014)
The development of technological innovation, driven by the internationalization process of companies, products and markets, is triggering major changes in economic performance, competition, in deregulation and in the revolution of knowledge. Realizing of essential importance to understand what function and role design plays in the national furniture industry and to understand how its products are developed, the focus of this study is to identify culturally how the furniture industry in Alto Uruguai/RS operates in relation to the design and propose actions to implement the Design Management, aiming to the effectuation of the design and improvement of quality in the companies. The work was supported by bibliographic and documental resources, structured and semi-structured interviews and also by fieldwork. The research showed that the vast majority of companies demonstrate to understand the importance of design for the development of its products; however, there are few that invest in its accomplishment. Therefore, the design management, being a means of integration and interaction of different areas, can reverse this situation by promoting in the companies the competitive differential that is so necessary for their survival, such as the economic development in the region in which it operates.